Diagnosing and Forecasting the Prospects for the Development of the Global Container Transportation Market - D. V. Malashchuk; N. A. Hrynchak (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The main trend in the development of domestic and global transport is the rapid growth of container traffic, which meets the requirements of a market economy. They become an integral part of the national or international commodity distribution and warehouse system, which ensures the uninterrupted delivery of various products to the trading network and goods of industrial and technical purpose to industrial production. According to experts from many countries, such transportation should embody the freight transport service of the XXI century. The growing demand for container transportation in Ukraine and in the world by manufacturers and consumers of various types of products and services requires the search for effective technical, technological and organizational solutions.A promising direction of container transportation is a unified system of container terminals (CT) created on the traffic routes of container-transportable cargoes. In addition, the problem of improving the quality of service due to the increased competition from other categories of transport is of particular importance.In a market economy and industry restructuring, there is a need for a new approach to address these issues, which would allow for reducing the cost of container ports and increasing their attractiveness for users. The importance of addressing these issues for the container transport industry determines the importance of this study.Topical problems of the current state and developments of the global market of container transportations are discussed. The largest container ports in the world are determined using the data on their throughput and the dynamics of the total capacity of container vessels in the maritime trade. The data on operation of the largest shipping companies in the world are analyzed. Index Baltic Dry is proposed for forecasting the global market of container transportations, which measures traffic volumes of bulk carriers; it is proposed to create support container terminals for the largest companies that would represent a single system of alliances rather than an isolated transport and logistics company.